Preservation of Lingual Nerve In Excision Of Bilateral Submandibular Sialolith Via Intraoral Approach: A Case Report - Mamat, Mohd Shaiful Nizam; Ibrahim, Rohaida; Abdullah, Baharudin (International Journal of Human and Health Sciences (IJHHS), 2018)
Salivary gland stone (sialolithiasis) is most common disease of the salivary gland and mainly occur at the submandibular gland. Traditionally, sialolithiasis is removed via an extra-oral approach but the major disadvantages of this treatment include a risk of injuring the lingul nerve, marginal mandibular nerve and scar formation. In this case report, we revealed an even less invasive intraoral surgical technique for the removal of sialolith that does not affect the submandibular gland function with the preservation of lingual nerve. This report describes a patient who had unusual bilateral submandibular gland sialolith that posteriorly located,which successfully removed via intraoral approach without any postoperative complications. International Journal of Human and Health Sciences Vol. 02 No. 03 July’18. Page : 161-163